Integrating Religious Considerations In End-of-life Care In Malaysia: An Ethico-legal Perspective - Fadhlina Alias; Ksssim, Puteri Nemie Jahn ,; Baharuddin, Ahmad Syukran (Peeters Online Journals, 2024)
Indexed by ERA